Is Voting the Only Mark of Patriotism? Youth Perspective in Zambia - Oliver, Magasu; Lucy, Kamboni; Lubbungu, Jive; Bwalya, Chilufya Lewis; Lackson, Lungu (Research Developments in Arts and Social Studies Vol. 5, 2022)
The goal of this study was to determine the level of patriotism among Zambian youngsters and whether voting is the only way for them to display their patriotism. One of the most important findings was that teenagers were able to define patriotism, even if it appeared to be hyperbole. Voting is not the only method to demonstrate patriotism; it is merely one of many options. Patriotism was defined as an emotional devotion to a country. Patriotism should be founded in the ideals that give birth to a country. Based on the findings, this chapter advises the government to reinforce patriotic ideals in schools, beginning in kindergarten, through the Ministry of Education. In Zambia, civil society organizations should develop patriotism awareness programs for youths.